A comparative study of accounting standards in China and Singapore. - Huang, Zhao Hong. (2009)
This study investigates the comparative differences of accounting standards between China and Singapore. The scope of comparison covers environmental circumstances, such as social climate, legal and political systems, economic conditions, securities exchange, taxation, auditing and accounting profession; accounting standards-setting process; accounting standards structure/components, accounting standards and financial reporting. The results indicate that the two countries' accounting standards are different in the accounting standards structure/components, accounting treatment, complexity of accounting standards, and disclosure requirements on financial information. Our first finding shows that the pattern of China's new accounting standards is a combination of macro management orientation and investor orientation. The rigid pursuit of historical cost in China is another finding. The third important finding in the study is that the disclosure requirement under China's new accounting standards is insufficient for effective disclosure of financial information, which is verified by our empirical study on financial reporting practice of twenty-six companies incorporated both in China and Singapore. We conclude that China's new accounting standards are relatively simple and ambiguous. It is still in its infancy as compared to the international accounting standards. We believe that there is scope for further improvement in China's accounting system to better serve the needs of the fastgrowing economy in China.